2014
DOI: 10.1371/journal.pone.0087245
|View full text |Cite
|
Sign up to set email alerts
|

Signals of Climate Change in Butterfly Communities in a Mediterranean Protected Area

Abstract: The European protected-area network will cease to be efficient for biodiversity conservation, particularly in the Mediterranean region, if species are driven out of protected areas by climate warming. Yet, no empirical evidence of how climate change influences ecological communities in Mediterranean nature reserves really exists. Here, we examine long-term (1998–2011/2012) and short-term (2011–2012) changes in the butterfly fauna of Dadia National Park (Greece) by revisiting 21 and 18 transects in 2011 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 50 publications
4
52
0
1
Order By: Relevance
“…Dadia NP is located in the east Mediterranean where extreme summer temperatures are anticipated in the future (Lelieveld et al, 2014). The rise of local temperature previously found (Zografou et al, 2014) might lead to multiple broods and prolonged flight periods (Haeler et al, 2014), but also it might intensify the extreme dry summer of the Mediterranean, causing ecological consequences to butterfly populations in Dadia NP by limiting adult nectaring and/or food availability (González-Estébanez et al, 2011). Trotta et al (2006) in their experiments showed that a short-lived invertebrate (Drosophila melanogaster Meigen) lived up to 29 days when raised at 31.2 ∘ C, whereas flies from the same population lived up to 247 days when reared at 12 ∘ C. In contrast, Maniola jurtina Linnaeus butterflies in Mediterranean, resulted in extremely prolonged life spans of females under continuous summer conditions (Haeler et al, 2014).…”
Section: Phenological Changementioning
confidence: 90%
See 3 more Smart Citations
“…Dadia NP is located in the east Mediterranean where extreme summer temperatures are anticipated in the future (Lelieveld et al, 2014). The rise of local temperature previously found (Zografou et al, 2014) might lead to multiple broods and prolonged flight periods (Haeler et al, 2014), but also it might intensify the extreme dry summer of the Mediterranean, causing ecological consequences to butterfly populations in Dadia NP by limiting adult nectaring and/or food availability (González-Estébanez et al, 2011). Trotta et al (2006) in their experiments showed that a short-lived invertebrate (Drosophila melanogaster Meigen) lived up to 29 days when raised at 31.2 ∘ C, whereas flies from the same population lived up to 247 days when reared at 12 ∘ C. In contrast, Maniola jurtina Linnaeus butterflies in Mediterranean, resulted in extremely prolonged life spans of females under continuous summer conditions (Haeler et al, 2014).…”
Section: Phenological Changementioning
confidence: 90%
“…The climate is sub-Mediterranean, with a mean annual rainfall of 652.9 mm, a mean annual temperature of 14.3 ∘ C, presenting a minimum in January and a maximum in July-August, while the arid summer season extents from July to September (25 ∘ C, 210 mm) (Maris & Vasileiou, 2010). Along with the dry and hot summers that characterise Dadia NP, a significant increase of temperature by 0.95 ∘ C has been documented for a 22-year-period (1990-2012) (Zografou et al, 2014). The Dadia area was established as a nature reserve in 1980 mainly owing to its great variety of birds of prey, and since then it has been recognised for its high biodiversity value for other taxa (Korakis et al, 2006;Kati et al, 2007;Schindler et al, 2008), including invertebrates (Grill & Cleary, 2003;Kati et al, 2004Kati et al, , 2007Argyropoulou et al, 2005;Korakis et al, 2006;Schindler et al, 2013).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The area is dominated by extensive pine and oak forest, but also contains a variety of other habitats such as pastures, arable land, torrents and stony hills. Dadia NP is a local biodiversity hotspot and has a successful history of monitoring, research and management for the conservation of biodiversity (Catsadorakis and Källander, 2010;Kati et al, 2004a,b;Schindler, 2010;Schindler et al, 2011;Zografou et al, 2014).…”
Section: Study Area Species Data and Land Cover Datamentioning
confidence: 99%